Branched‐chain amino acids promote endothelial dysfunction through increased reactive oxygen species generation and inflammation. Issue 10 (31st July 2018) - Zhenyukh, Olha; González‐Amor, Maria; Rodrigues‐Diez, Raul R.; Esteban, Vanesa; Ruiz‐Ortega, Marta; Salaices, Mercedes; Mas, Sebastian; Briones, Ana M.; Egido, Jesus
Abstract: Branched‐chain amino acids (BCAA: leucine, isoleucine and valine) are essential amino acids implicated in glucose metabolism and maintenance of correct brain function. Elevated BCAA levels can promote an inflammatory response in peripheral blood mononuclear cells. However, there are no studies analysing the direct effects of BCAA on endothelial cells (ECs) and its possible modulation of vascular function. In vitro and ex vivo studies were performed in human ECs and aorta from male C57BL/6J mice, respectively. In ECs, BCAA (6 mmol/L) increased eNOS expression, reactive oxygen species production by mitochondria and NADPH oxidases, peroxynitrite formation and nitrotyrosine expression. Moreover, BCAA induced pro‐inflammatory responses through the transcription factor NF‐κB that resulted in the release of intracellular adhesion molecule‐1 and E‐selectin conferring endothelial activation and adhesion capacity to inflammatory cells. Pharmacological inhibition of mTORC1 intracellular signalling pathway decreased BCAA‐induced pro‐oxidant and pro‐inflammatory effects in ECs. In isolated murine aorta, BCAA elicited vasoconstrictor responses, particularly in pre‐contracted vessels and after NO synthase blockade, and triggered endothelial dysfunction, effects that were inhibited by different antioxidants, further demonstrating the potential of BCAA to induce oxidative stress with functional impact. In summary, we demonstrate that elevated BCAA levels generate inflammation and oxidative stress in ECs, thereby facilitating inflammatory cells adhesion and endothelial dysfunction. This might contribute to the increased cardiovascular risk observed in patients with elevated BCAA blood levels.